Resilience Predicts Social Functioning in Clinically Stable Patients With Bipolar Disorder. Issue 7 (July 2018) - Bozikas, Vasilis P.; Parlapani, Eleni; Ntouros, Evangelos; Bargiota, Stavroula I.; Floros, Georgios; Nazlidou, Elena I.; Garyfallos, Georgios
Abstract : Abstract: The current study focused on the association between resilience and social functioning in patients with bipolar disorder (BD). Forty clinically stable patients with BD type I and BD type II, as well as 40 healthy controls, matched for age, sex, and educational background were enrolled. Clinical status was assessed by the Montgomery-Åsberg Depression Rating Scale and the Young Mania Rating Scale. Functioning was evaluated by the Mini International Classification of Functioning, Disability and Health rating of activities and participation in mental illnesses, and the Social and Occupational Functioning Scale. Resilience was measured by the Connor-Davidson Resilience scale. Patients demonstrated significantly lower resilience levels compared with healthy individuals. A stepwise regression analysis indicated that only resilience contributed significantly to social functioning's outcome. Because resilience may constitute a social functioning moderator in clinically stable patients with BD, a paradigm shift toward protective factors could lead to implementation of resilience-oriented interventions designed specifically for patients with BD.